The Effect of Religious Value-Based Reaction Rate Teaching Materials on Student Learning Outcomes Using The Guided Inquiry Model - Haz, Emalia Syafitri; Darmana, Ayi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
This study aims to determine (1) whether there is an effect in the form of differences between student learning outcomes using reaction rate chemistry teaching materials integrated with religious values using chemistry teaching materials SMA / MA with guided inquiry models, (2) whether there are differences in students' spiritual attitudes before and after being taught with teaching materials integrated with religious values, (3) is there a relationship between improving student learning outcomes on reaction rate material with students' spiritual attitudes. The sample in this study consisted of two classes, namely the experimental class and the control class. The research instrument was a multiple choice test of 20 valid and reliable items (0.862) and a spiritual attitude questionnaire. The data analysis used is the Mann-Whitney Test non-parametric test with a significance level of 0.05l, Paired Sample T-Test test, and correlation. The results of research and testing show the ability of student learning outcomes taught using teaching materials for reaction rates integrated with religious values using guided inquiry learning models is higher than using high school / MA Chemistry teaching materials with guided inquiry models, namely (0.037 <0.05), teaching materials for reaction rates integrated with religious values provide positive value to students, and there is a significant relationship between learning outcomes and students' spiritual attitudes of 0.461 in the moderate category.